In vitro antifungal susceptibilities of isolates of Candida spp. and Aspergillus spp. from China to nine systemically active antifungal agents: data from the SENTRY antifungal surveillance program, 2010 through 2012. Issue 4 (27th February 2015) - Pfaller, Michael A.; Castanheira, Mariana; Messer, Shawn A.; Jones, Ronald N.
Summary We report the in vitro activity of nine systemically active antifungal agents against 237 contemporary clinical isolates of yeast and moulds obtained from 13 laboratories in China during 2010 through 2012. Susceptibility testing was performed using CLSI methods. Sequencing of fks hot spots was performed for echinocandin non‐wild‐type (WT) strains. Isolates included 220 from eight species of Candida, 15 from four species of Aspergillus and one isolate each of Rhodotorula mucilaginosa and Trichosporon asahii. Resistance to amphotericin B (0.0%), flucytosine (0.0–1.7%) and the echinocandins (0.0–3.4%) was distinctly uncommon among C. albicans, C. parapsilosis, C. tropicalis, C. glabrata and C. pelliculosa. Three C. albicans isolates showed resistance to echinocandins and one harboured a mutation in HS1 of fks1. Resistance to the azoles was much more common with resistance to fluconazole, voriconazole and posaconazole detected among isolates of C. glabrata and C. tropicalis. Both C. parapsilosis and C. pelliculosa exhibited decreased susceptibility to fluconazole. Amphotericin B, the mould‐active azoles and the echinocandins were all quite active against isolates of A. fumigatus and A. flavus. Consistent with previous studies from China, resistance to fluconazole is prominent among Candida spp. isolates in this country.